2019
DOI: 10.1021/acs.inorgchem.9b00194
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Pyran Formation in the Molybdenum Cofactor: Protonation of Quinoxalyl–Dithiolene Promoting Pyran Cyclization

Abstract: Mononuclear Mo and W enzymes require a unique ligand known as molybdopterin (MPT). This ligand binds the metal through a dithiolene chelate, and the dithiolene bridges a reduced pyranopterin group. Pyran scission and formation has been proposed as a reaction of the MPT ligand that may occur within the enzymes to adjust reactivity at the Mo atom. We address this issue by investigating oxo-Mo(IV) model complexes containing dithiolenes substituted by pterin or quinoxaline, and a hydroxyalkyl poised to form a pyra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
(124 reference statements)
1
9
0
Order By: Relevance
“…This interpretation is consistent with our previous work with a molybdenum quinoxaline dithiolene analogue of 1, in which we reported that addition of TFAA induces pyran ring cyclization and produces a similar intense red-shifted absorption. 75 However, the outcome in that study differed because quinoxaline protonation resulted in a loss of the hydroxyl group that triggered an intramolecular cyclization to form a pyrrolo-pterin dithiolene ligand. Hence, these results also serve to underscore the differences between pterin and quinoxaline and how the use of quinoxaline as a simpler heterocycle mimic of pterin may not show the full scope of reactivity.…”
Section: ■ Relationship To Pyranopterin Mo Enzymesmentioning
confidence: 97%
See 1 more Smart Citation
“…This interpretation is consistent with our previous work with a molybdenum quinoxaline dithiolene analogue of 1, in which we reported that addition of TFAA induces pyran ring cyclization and produces a similar intense red-shifted absorption. 75 However, the outcome in that study differed because quinoxaline protonation resulted in a loss of the hydroxyl group that triggered an intramolecular cyclization to form a pyrrolo-pterin dithiolene ligand. Hence, these results also serve to underscore the differences between pterin and quinoxaline and how the use of quinoxaline as a simpler heterocycle mimic of pterin may not show the full scope of reactivity.…”
Section: ■ Relationship To Pyranopterin Mo Enzymesmentioning
confidence: 97%
“…Although a number of works have focused on how a dithiolene ligand bound to Mo can affect the Mo electronic structure and reduction potential, , , , there is a dearth of such studies on the contributions of pyranopterin and related dithiolenes to the modification and control of the electronic structure and reduction potential. ,,, In this work, we investigate the critical importance of the entire PDT moiety in model systems for Moco and report the consequences of pterin protonation in complexes 1–3 (Figure , middle), which represents a simple reaction that models how the transfer of a proton from neighboring acidic amino acid residues in the protein PDT binding pocket might impact the electronic structure of the Mo-PDT unit. Pterin protonation at position N5 exclusively stabilizes the pyranopterin structure and completely disfavors pyran ring opening.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, soon after the identification of Moco as a pterin derivative, pterin-inspired model chemistry started with the synthesis of pterin-substituted dithiolenes [ 58 ]. There are ongoing attempts for the total chemical synthesis of Moco [ 59 , 60 ]. However, it has not yet been achieved, although the chemical synthesis of Moco’s precursor, cPMP, has been successful [ 61 ].…”
Section: History Of Mocomentioning
confidence: 99%
“…The importance of the pyran ring of pyranopterin ligands is relevant to understanding the role of the MPT ligand in biological systems. Model compounds containing Mo coordinated by tris(3,5-dimethyl-1-pyrazolyl)borate (Tp*) and model MPT ligands ( Figure 5 ) have been reported and demonstrate the importance of pyran cyclization to intraligand electronic communication [ 54 , 55 ]. In both instances pyran cyclization is modulated by the presence of a hydroxyl group on the carbon α to the dithiolene unit of the model ligand.…”
Section: Impact Of Pyran Cyclization On Redox Chemistrymentioning
confidence: 99%
“…For both sets of model compounds, the redox potential for the Mo (V/IV) couple is more positive for compounds with pyran ring functionality. The redox couple observed for 3 is 115 mV more positive than 4 , whereas 5 is only 54 mV more positive than 6 [ 54 , 55 ]. The differences in reduction potentials observed for both ligand and metal-based redox processes indicates that pyran cyclization of the pyranopterin ligands can serve to electronically tune and modulate reactivity.…”
Section: Impact Of Pyran Cyclization On Redox Chemistrymentioning
confidence: 99%